AI and Course Work: Figuring out Ethical Strategies - Peters, Brian (Apprendre et enseigner aujourd’hui)

(untitled) (Conseil pédagogique interdisciplinaire du Québec, 2023)
At John Abbott and Concordia, many departmental discussions have been started addressing the scary and very real situation pertaining to AI and student work. At Concordia, one department that I know of has already circulated a working document about AI, outlining problems and strategies—this is what we need more of for sure. The English Department at Concordia has started meetings, and many discussions are taking place at the Cegep level on both the departmental and administrative levels. Is there anything we can really do, is a major question that I feel, for now, might not have an answer. What we do need to do is figure out how to address AI, how to find it/spot-it, and via our pedagogies how to motivate students not to use AI. In short, yes, we can—solutions are popping up to detect AI and, most of all, we need to make sure we don’t overload our own work schedules trying to outsmart students who use AI. This article presents an overview of obstacles that current course instructors face, be they tenured faculty, lecturers, non-permanent/part-time faculty, or teaching-assistants ; as well, this informal discussion of such problems and findings is the beginning to a discussion on how to manage course content and time without burning out as we navigate the often confusing realities associated with AI and the internet as a source where students can readily cheat and/or plagiarize.